Pengaruh obat amfetamin pada olahraga balap sepeda - Ananda Perwira Bakti, (Ilmu Keolahragaan, 2013)
Abstract : Doping is a substance or prohibited substances and methods to increase performance in sports that are not associated with a medical indication. Drug doping is a group that included stimulant, narcotic analgesics, anabolic steroid group, class betabloker, class of diuretics, and peptide groups hormons and analogues. Selection of amphetamines (stimulants) based on the number of athletes who abuse these types of drugs, especially in the branch of cycling. Amphetamines are substances that stimulate the central nervous system works. The use of amphetamines often consumed cyclist can cause effects such as increased alertness, reduce drowsiness, reduced fatigue, and increased motor activity (physical performance).   Key words : doping, amphetamines, cyclist.